Game analysis on constructing the model of an international carbon emissions trading model - Ming Ji (Chinese Journal of Population, Resources and Environment, 2021)
ABSTRACT: Constructing a model for international carbon emissions trading is an effective method to curb global warming through a market mechanism. Although the international carbon emissions market generates substantial profits, the relevant trading mechanism has been far from perfect. The perfect mechanism for international carbon emissions trading should be a revealing preference game. In other words, only if all players in this game truly show their information and preferences can the Nash outcome be Pareto efficient and fair. China should actively participate in the international carbon emissions trading game; promote efficiency, justice, rationality, and the quality of being manipulation-free in the carbon emissions market; and play a more important role in perfecting the international carbon emissions trading mechanism.